Identifying football conflict using soft-set theory in Indonesia super league / Kukuh Wahyudin Pratama - Kukuh Wahyudin , Pratama (2021)
There are several mathematical formal models that handle conflict situations and the most popular one is a rough set theory. With the ability to handle vagueness from the conflict data set, rough set theory has been successfully used in many research. This research used an alternative approach as a method to handle conflict situation in Indonesia Super League. This method was implemented on the respondents or agents who were involved with football club management, match inspector, organizing committee, referees, supporters and players. The novelty of the proposed approach is discussed in rough set theory that include decision rules. It is based on the concept of co-occurrence of parameters in soft set theory. Back in 2015, Indonesia has no an official football competition for almost a year when FIFA banned the Football Association of Indonesia for competing in any international competitions until the internal conflict among their agents were resolved. In managing the conflict situation and identifying the uncertainties, this research proposes a new approach of Computation Intelligence in handling football conflict using Soft Set Theory. Motivated from the fact that every rough set is a soft set, this research derived an alternative algorithm to identify conflict situations from the point of view of soft set theory. We then delineated the proposed algorithm for an instructional example of Indonesian football conflict situation concerning the Indonesia Football Super League. The results showed that the proposed algorithm has been successful in handling conflict and finally making recommendation to the Indonesian football agents involved.